Comparative potentials of native arbuscular mycorrhizal fungi to improve nutrient uptake and biomass of Sorghum bicolor Linn - Nakmee, Pattarawadee Sumthong; Techapinyawat, Sombun; Ngamprasit, Supranee (Agriculture and Natural Resources, 2016)
Sorghum (Sorghum bicolor Linn.) seedlings were grown in pots using Pakchong soil from Nakhon Ratchasima province. Ten species of native Arbuscular mycorrhizal (AM) fungi: Glomus sp. 1, Glomus sp. 2, Glomus sp. 3, Glomus aggregatum, Glomus fasciculatum, Acaulospora longula, Glomus occultum, Acaulospora scrobiculata, Acaulospora spinosa and Scutellospora sp., were used to inoculate sorghum seedlings. The sorghum growth and uptake of several major nutrients were evaluated at the harvesting stage. The results revealed that sorghum inoculated with A. scrobiculata produced the greatest biomass, grain dry weight and total nitrogen uptake in shoots. The highest phosphorus uptake in shoots was found in A. spinosa-inoculated plants, followed by Glomus sp. and A. scrobiculata, whereas Scutellospora sp.- inoculated plants showed the highest potassium uptake in shoots followed by A. scrobiculata. Overall, the most efficient AM fungi for improvement of nutrient uptake, biomass and grain dry weight in sorghum were A. scrobiculata.